Lobularia libyca (Viv.) Meisn. (Brassicaceae), a new species for the mainland portuguese flora - Neiva, João; Quinto-Canas, Ricardo; David, Manuela (Acta Botanica Malacitana, 2022)
The annual Lobularia libyca (Brassicaceae) is first described from mainland Portugal. A single isolated population, composed of fruiting individuals approaching the end of its life cycle, was found in Ria Formosa (Algarve, southern Portugal) in early 2022, and was estimated to be less than 120 reproductive individuals. The native status and apparent rarity of the species, or at least of records, in the region, are discussed.